Disseminated histiocytic sarcoma in a Labrador retriever in Brazil - Gonçalves, Saulo R. F.; Barretto, Mariana L. M.; Silva, Débora M. S. da; Albuquerque, Pedro P. F. de; Barros, Alessandra V. de; Bezerra, Letícia M.; Filho, Almir A. S.; Santos, Edna M. S.; Oliveira, Andrea A. F.; Souza, Francisco A. L. (Brazilian Journal of Veterinary Pathology, 2019)
Histiocytic sarcoma (HS) refers to a rare neoplasm of round cells frequently presented in a disseminated form, affecting bones, joints, skin, and subcutaneous tissue. The objective of this study was to report a case of disseminated HS in a canine attended at HOVET-UFRPE, Recife, Brazil. Physical examination and complementary tests were performed; complete blood count and serum biochemistry were normal, but at thoracic radiography exam a neoformation was detected in the right lung. Cytopathological evaluation was suggestive of malignant epithelial neoplasia. At necropsy, there were disseminated nodules in the lungs, liver, spleen, kidneys, meninges and eye. The histopathological examination revealed proliferation of pleomorphic round cells, suggesting HS, which was confirmed by immunohistochemistry. From the obtained results, it becomes evident the importance of complementary exams to properly diagnose histiocytic diseases. This is one of the few reports of canine disseminated HS in Brazil.